In silico maturation of binding‐specificity of DNA aptamers against Proteus mirabilis. Issue 10 (22nd April 2013) - Savory, Nasa; Lednor, Danielle; Tsukakoshi, Kaori; Abe, Koichi; Yoshida, Wataru; Ferri, Stefano; Jones, Brian V; Ikebukuro, Kazunori
ABSTRACT Proteus mirabilis is a prominent cause of catheter‐associated urinary tract infections (CAUTIs) among patients undergoing long‐term bladder catheterization. There are currently no effective means of preventing P. mirabilis infections, and strategies for prophylaxis and rapid early diagnosis are urgently required. Aptamers offer significant potential for development of countermeasures against P. mirabilis CAUTI and are an ideal class of molecules for the development of diagnostics and therapeutics. Here we demonstrate the application of Cell‐SELEX to identify DNA aptamers that show high affinity for P. mirabilis. While the aptamers identified displayed high affinity for P. mirabilis cells in dot blotting assays, they also bound to other uropathogenic bacteria. To improve aptamer specificity for P. mirabilis, an in silico maturation (ISM) approach was employed. Two cycles of ISM allowed the identification of an aptamer showing 36% higher specificity, evaluated as a ratio of binding signal for P. mirabilis to that for Escherichia coli (also a cause of CAUTI and the most common urinary tract pathogen). Aptamers that specifically recognize P. mirabilis would have diagnostic and therapeutic values and constitute useful tools for studying membrane‐associated proteins in this organism. Biotechnol. Bioeng. 2013;110: 2573–2580. © 2013 Wiley Periodicals, Inc.